2008
DOI: 10.1186/1743-7075-5-28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dairy intake on weight maintenance

Abstract: Background: To compare the effects of low versus recommended levels of dairy intake on weight maintenance and body composition subsequent to weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 44 publications
(57 reference statements)
5
64
0
4
Order By: Relevance
“…; therefore, we did not include them in metaanalysis. 35,41 For five studies 27,30--32,34 included in meta-analysis, participants' age ranged between 18 and 85 years. Duration of intervention varied between 21 and 48 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…; therefore, we did not include them in metaanalysis. 35,41 For five studies 27,30--32,34 included in meta-analysis, participants' age ranged between 18 and 85 years. Duration of intervention varied between 21 and 48 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…We found that two papers, 33,41 which administered energy restriction, had confined the energy intake into a defined certain value in both intervention and control groups, whereas other studies restricted the energy intake of participants to the amount of 500 kcal less than their computed daily energy requirement. Because restriction of energy to fixed values can directly affect weight change, 33,41 we preferred not to include the results of these two studies in the systematic review and meta-analysis; however, findings from the maintenance phase of study done by Zemel et al 41 were included in our systematic review. Besides restriction of energy intake to a fixed value, these two studies had some other distinct features.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…This study was part of a larger randomized, clinical trial that evaluated the effects of moderate weight loss and subsequent weight stabilization on either a low-or recommended-dairy weight-maintenance diet on body weight, body composition and metabolic fitness (Zemel et al, 2008). All participants were prescribed a reduced energy diet designed to result in, at least, a 10% reduction in initial body weight during the 12-week weight-loss phase of the study.…”
Section: Experimental Designmentioning
confidence: 99%